Genetic Etiology Investigation in Treatment-Resistant Nocturnal Enuresis Children: A descriptive study - Yener, Sevim; Eser, Metin (Urology Journal, 2025)
Purpose: Our study aimed to evaluate the genetic etiology of treatment-resistant nocturnal enuresis in children who have undergone at least 6 episodes of behavioral therapy, urotherapy, alarm therapy, and medical treatment. Materials and Methods: A total of 21 patients were included in the study. Inclusion criteria for the study comprised children aged 5-18 years diagnosed with treatment-resistant enuresis according to the International Children’s Continence Society (ICCS) guidelines. The capture-based Sophia Hereditary Disease Panel by Sophia Genetics was used specifically for nocturnal enuresis, consisting of a panel of 19 genes (AGXT, AQP2, AVPR2, BNC2, CLCNKB, DLG3, ELN, FA2H, FAM20A, FOXP1, HPSE2, KCNJ10, MLXIPL, NPHP3, RNF168, SLC12A3, SLC25A13, SLC5A2, SMARCA2). Results: Patients were analyzed for genetic variations in genes associated with nocturnal enuresis, including AGXT, AQP2, AVPR2, BNC2, CLCNKB, DLG3, ELN, FA2H, FAM20A, FOXP1, HPSE2, KCNJ10, MLXIPL, NPHP3, RNF168, SLC12A3, SLC25A13, SLC5A2, and SMARCA2. No pathogenic changes potentially explaining the etiology of the disease were detected in 20 patients. One patient exhibited a variant in the AQP2 gene at hg19:Chr12:50344908 exon 1, c.295G>A locus, classified as a Variant of Uncertain Significance (VUS) according to the American College of Medical Genetic and Genomics (ACMG) 2015 guidelines. The AQP2 gene is associated with autosomal dominant and autosomal recessive inherited nephrogenic diabetes insipidus (type 2) in the OMIM (Online Mendelian Inheritance in Man) database. Conclusion: Our study resembles studies indicating that nocturnal enuresis cases do not have a monogenic etiology but occur with multifactorial effects and have a weak correlation between genotype and phenotype.